Setor agropecuário brasileiro pós-novo código florestal: Uma simulaç\~ao de impactos econômicos - Mari Aparecida dos Santos; Joaquim Bento de Souza Ferreira Filho; José Eustáquio Ribeiro Vieira Filho; Alexandre Xavier de Carvalho Ywata (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The objective of this research was to compare the economic impacts, in Brazil, of the New Forest Code considering two possible scenarios: in the first case there is no Environmental Reserve Quotas (ERQ); and in the second case there is no amnesty to small landowners. The methodology integrates two models: Globiom-Brazil and Term-BR. The results showed that the impacts in the value of macroeconomic aggregates, in the cumulative period from 2005 to 2030, compared to the baseline, for the first (without ERQ) and second scenario (without amnesty), respectively decrease in: 0.12% and 0.51% in real GDP; 0.11% and 0.43% in consumption; 0.11% and 0.45% in government expenditure; 0.84% and 3.09% in real investment; 0.14% and 0.4% in imports. Although, for the same period of analysis, there were exports increased by 0.43% and 1.89%. In the first scenario, the most economically affected state was Mato Grosso (-4.52% in GDP) and in the second scenario Goias (-4.25% in GDP). In addition, it was observed that soy and cattle breeding are the most negatively affected by such changes in environmental policy.
Keywords: Q1; Q5; Q51; 330; economic impacts; New Forest Code; Globiom-Brazil; Term-BR